Outside Training of Spanish University Students of Education for the Didactic Application of Cinema: Formal, Non-Formal, and Informal Perspectives - Alejandro Lorenzo-Lledó; Asunción Lledó; Gonzalo Lorenzo; Alba Gilabert-Cerdá (MDPI AG, 2022)
Nowadays, audiovisual media play a central role in access to information and in personal relationships. Among the audiovisual media is cinema, which due to its heterogeneous nature, can fulfill diverse educational functions. The objective of this study was to learn about the training that future teachers in Spain receive outside of their teaching degree for the didactic use of cinema. In addition, we sought to understand the influence of training on perceptions regarding the educational potential of cinema and the predisposition to its use. Using a quantitative approach, information was collected from 4659 students from 58 Spanish universities. The questionnaire used covered perceptions about the potencialities of cinema as a didactic resource in pre-school and primary classrooms (PECID). The results showed that 95.1% of the students had not received training. In addition, we found a significant influence of training on their perceptions of the educational possibilities of cinema. Furthermore, we found an influence on their predisposition to use training in their future teaching practice. Overall, it is necessary to implement training actions to fill the gaps detected in favor of a quality education with active learning and linked to society.